Optimization of In Vitro Culture Conditions of Sturgeon Germ Cells for Purpose of Surrogate Production - Xie, Xuan; Li, Ping; Pšenička, Martin; Ye, Huan; Steinbach, Christoph; Li, Chuangju; Wei, Qiwei (Animals, 2019)
To expand germ cell populations and provide a consistent supply for transplantation, we established basal culture conditions for sturgeon germ cells and subsequently increased their mitotic activity by eliminating gonad somatic cells, supplementing with growth factor, and replacing fetal bovine serum (FBS). The initial basal culture conditions were Leibovitz's L-15 medium (pH 8.0) supplemented with 5% FBS (p < 0.001) at 21 °C. Proliferation of germ cells was significantly enhanced and maintained for longer periods by elimination of gonad somatic cells and culture under feeder-cell free conditions, with addition of leukemia inhibitory factor and glial-cell-derived neurotrophic factor (p < 0.001). A serum-free culture medium improved germ cell proliferation compared to the L-15 with FBS (p < 0.05). Morphology remained similar to that of fresh germ cells for at least 40 d culture. Germline-specific gene expression analysis revealed no significant changes to germ cells before and after culture. Sterlet Acipenser ruthenus germ cells cultured more than 40 days showed development after transplant into Russian sturgeon Acipenser gueldenstaedtii. Polymerase chain reaction showed 33.3% of recipient gonads to contain sterlet cells after four months. This study developed optimal culture condition for sturgeon germ cells. Germ cells after 40 d culture developed in recipient gonads. This study provided useful information for culture of sturgeon germ cells.
Keywords: transplantation; glial-cell-derived neurotrophic factor; sturgeon; germ cell culture; feeder cells